RESPONSE OF YAM (Dioscorea spp.) ACCESSIONS TO DROUGHT AND ARBUSCULAR MYCORRHIZAL FUNGI (2016)
Moisture deficit limits yam production. Availability of drought tolerant yam will improve yield and expand area of production. Soil inoculation with Arbuscular Mycorrhizae Fungi (AMF) improves tolerance of plants to drought. However, there is limited information on the response of yam to drought and AMF inoculum. This study was conducted to identify drought tolerant yam accessions and determine the effects of AMF.Two glasshouse and one field experiments were conducted, each in a randomized complete block design with three blocks. In the first glasshouse experiment, 32 accessions of Dioscorea alata and 49 of D. rotundata obtained from the International Institute of Tropical Agriculture, Ibadan were screened for drought tolerance. Pre-sprouted setts were planted in pots containing 5 kg soil, watered to Field Capacity (FC), wrapped with transparent polyethylene sheets and observed for 90 days. Twelve accessions of each species selected on the basis of their superior performance were further evaluated at three moisture levels: 75% FC at 11 Weeks After Planting (WAP) 25% FC at 15 WAP and 25% FC at 11 WAP,with and without AMF inoculation. Three promising drought tolerant accessions of each species were selected from the second experiment and evaluated in the field. Treatments were two irrigation intervals with 12 mm water (four-day and monthly), three planting dates (monthly: July, August, September) and AMF inoculations (with and without) laid out as split-split-split plot. Data were collected on Fresh and Dry Tuber Weight (FTW and DTW), Harvest Index (HI), mycorrhizal colonisation and number of AMF spores. Data were analysed using descriptive statistics, correlation and ANOVA at α 0.05.The accessions differed significantly in their response to water- and AMF- levels for most growth and yield parameters. The FTW per plant ranged from 24.0±7.7 g (TDa02/00012) to 54.0±10.0 g (TDa297) in D. alata and 13.0±1.8 g (TDr99/02789) to 57.0±9.2 g (TDrAbi) in D. rotundata. Drought stress at 25% FC, 11 WAP resulted in 83% reduction in FTW as compared to a decline of 67.8% at 25% FC, 15 WAP in D. alata. Mycorrhizal inoculation significantly increased the FTW by 58% and DTW by 112% for D. alata while increases of 33% and 38%, respectively were recorded for D. rotundata. The FTW (D. alata and D. rotundata) was significantly correlated with DTW (r= 0.89, 0.91), HI (r= 0.80, 0.78), number of AMF spores (r= 0.53, 0.55) and mycorrhizal colonisation (r= 0.32, 0.30) respectively. In the field, irrigation at four-day intervals improved tuber yield of D. rotundata by 50% relative to monthly irrigation. The highest FTW (10±0.7 t/ha) for D. alata was obtained with the July planting while the September planting had the least (3±0.7 t/ha). Across treatments, accessions TDa02/00012 of D. alata and TDrSaminaka of D. rotundata had the highest FTW of 7.0±1.0 t/ha and 5.0±1.0 t/ha, respectively.Variation for drought tolerance exists among D. alata and D. rotundata accessions studied. Mycorrhizal inoculation improved yam yield under moisture stress. Accessions TDa02/00012, TDa93-36, TDaKesofunfun of D. alata and TDrSaminaka, TDrAloshi, TDrAbi of D. rotundata were most drought tolerant